Studi Analisis tentang Kompetensi Kepala Madrasah dalam Mewujudkan Madrasah Unggul di Madrasah Aliyah Unggulan STEP-2 IDB Darul 'Ulum Jombang - Suwandi (Universitas Hasyim Asy'ari (UNHASY) Tebuireng Jombang, 2018)
Since the enactment of Law No.20 of 2003 concerning the National education system which places madrasas as part of the national education sub-system. Madrasas are also required to innovate and renew themselves, both institutionally and in terms of their output quality. The output quality is expected to have been conceptualized in Article 31 paragraph 3 of the 1945 Constitution which states that the government undertakes and organizes a national education system that enhances faith and devotion and noble morality. This concept has a purpose to educate the life of the nation where it puts hope and aspirations that an educational institution must be able to bring and direct students to have faith, piety and noble morality. So that they are intelligent both intellectually, morally and spiritually. Madrasas as educational institutions have the task of preparing and developing quality human resources in the field of IMTAQ and science and technology that need to be accompanied by breakthroughs and up to date innovations to facilitate the birth of superior output. Thus, the head of the madrasa is fully demanded to be the head of a professional and competent madrasa in order to create a superior madrasa (madrasah unggulan). Based on the existing phenomena, the focus of this study was formulated on the competencies of the head of the madrasa and superior madrasas in the Madrasah Aliyah Unggulan Darul ‘Ulum Jombang with the following objectives: (1) to find out the steps in realizing superior madrasas; (2) to find out the competence of the madrasa principals in realizing superior madrasas; and (3) to find out the supporting and inhibiting factors in realizing superior madrasas. The type of research used is field research, because this research is based on data collected from the field directly. Based on the research method, the researcher uses descriptive method research that is describing, recording, analyzing, interpreting the conditions that occur now in the field. With qualitative research, it is expected that the sharpness of the analysis will be obtained. From the results of the study it can be concluded that: (1) Structurally Madrasah Aliyah Unggulan Darul 'Ulum Jombang has fulfilled the standards of superior madrasas and still exists in the midst of other institutions both in terms of student affairs, teacher professionalism, curriculum, facilities and trust support provided by the community; (2) Head of Madrasah Aliyah Unggulan Darul 'Ulum Jombang has met competency standards in its achievement to develop an Islamic education institution